Gray Matter Alterations in Post-Traumatic Stress Disorder, Obsessive–Compulsive Disorder, and Social Anxiety Disorder - Cheng, Bochao; Huang, Xiaoqi; Li, Shiguang; Hu, Xinyu; Luo, Ya; Wang, Xiuli; Yang, Xun; Qiu, Changjian; Yang, Yanchun; Zhang, Wei; Bi, Feng; Roberts, Neil; et al. (Frontiers in Behavioral Neuroscience, 2015)
Post-traumatic stress disorder (PTSD), obsessive-compulsive disorder (OCD) and social anxiety disorder (SAD) all bear the core symptom of anxiety and are separately classified in the new DSM-5 system. The aim of the present study is to obtain evidence for neuroanatomical difference for these disorders. We applied voxel-based morphometry (VBM) with Diffeomorphic Anatomic Registration Through Exponentiated Lie (DARTEL) to compare grey matter volume (GMV) in Magnetic Resonance (MR) images obtained for thirty patients with PTSD, twenty nine patients with OCD, twenty patients with SAD and thirty healthy controls. GMV across all four groups differed in left hypothalamus and left inferior parietal lobule and post hoc analyses revealed that this difference is primarily due to reduced GMV in the PTSD group relative to the other groups. Further analysis revealed that the PTSD group also showed reduced GMV in frontal lobe, temporal lobe and cerebellum compared to the OCD group, and reduced GMV in frontal lobes bilaterally compared to SAD group. A significant negative correlation with anxiety symptoms is observed for GMV in left hypothalamus in three disorder groups. We have thus found evidence for brain structure differences that in future could provide biomarkers to potentially support classification of these disorders using MRI.